Clinical Outcomes and Quality of Life According to Types of Reconstruction Following Laparoscopy-assisted Distal Gastrectomy for Gastric Cancer. Issue 1 (February 2015) - Komatsu, Shuhei; Ichikawa, Daisuke; Kubota, Takeshi; Okamoto, Kazuma; Shiozaki, Atsushi; Fujiwara, Hitoshi; Konishi, Hirotaka; Morimura, Ryo; Murayama, Yasutoshi; Kuriu, Yoshiaki; Ikoma, Hisashi; Nakanishi, Masayoshi; et al.
Abstract : Purposes: Laparoscopy-assisted distal gastrectomy (LADG) has gained wide acceptance and is being more commonly performed at the period of introduction. This study was designed to determine the clinical outcomes and quality of life (QOL) according to types of reconstruction following LADG for gastric cancer. Patients and Methods: Between 2007 and 2010, 117 consecutive patients underwent LADG. These patients were classified into 2 groups: Billroth-I group (n=74) and Roux-en-Y group (n=48). Results: Although there were no significant differences in background factors such as sex, body mass index, pN stage, pT stage, or extent of lymphadenectomy between both the groups, patients with Billroth-I reconstruction were found more frequently in the lower portion of gastric cancer ( P =0.0173), shorter surgical durations ( P <0.0001), and less blood loss ( P <0.0001). The overall postoperative complication rates did not significantly differ between both the groups ( P =0.0675). However, the incidence of patients with postoperative stasis ( P =0.0170) and long hospital stay ( P =0.0039) was significantly higher in patients with Roux-en-Y reconstruction. Concerning the evaluation of long-term QOL using the Gastrointestinal Symptom Rating Scale, there were no significant differences in total score between both the groups ( P =0.4387). Conclusions: Billroth-I technique might comparatively be accessible and safe in the reconstruction of LADG. However, the differences of reconstruction do not affect long-term QOL.